CyDER – an FMI-based co-simulation platform for distributed energy resources. Issue 5 (3rd September 2019) - Nouidui, Thierry S.; Coignard, Jonathan; Gehbauer, Christoph; Wetter, Michael; Joo, Jhi-Young; Vrettos, Evangelos
Abstract : The increased integration of distributed energy resources (DERs) is bringing a number of challenges to the power grid. These include reverse power flows in distribution systems and potentially transmission systems and grid stability. So far, specialized tools have been developed to capture some of the impact of DERs at the distribution level. However, distribution system operators lack visibility into the overall system conditions. Furthermore, the impact of increasing DERs is not limited to the distribution level but also influences the transmission grid. To support the planning and operation of the grid, we developed a co-simulation platform called CyDER (A Cyber Physical Co-simulation Platform for Distributed Energy Resources in Smart Grids) that integrates various domain-specific simulation tools. CyDER is based on the functional mock-up interface standard. This paper gives an overview of CyDER and demonstrates its use based on two applications.